Status of beta defensin-1 in Indian goat breeds - RANJAN, R; SINGH, S P; GURURAJ, K; JINDAL, S K; CHAUHAN, M S (The Indian Journal of Animal Sciences, 2019)
The present study was carried out to know the status of Beta Defensin-1 in goat semen before and after cryopreservation with beta defensin-1 supplemented semen diluent and in blood of different breeds of goat (Barbari, Jamunapari and Jakhrana). Goat semen (N-10) from each breed was collected by artificial vagina method. Immediately after collection, the volume, colour, consistency, and mass motility of ejaculate were assessed and were extended with Tris-Egg yolk-Fructose diluent having 10% (v/v) egg yolk and glycerol 6% (v/v). Samples were divided for estimation of beta defensin–1 and rest parts were cryopreserved with semen diluent having beta defensin-1 @ 10 ng/mL. Blood samples (N-30) were also collected from the same animal after semen collection. The samples were stored at –20°C until assayed. Plasma membrane of sperm was broken by freeze thaw followed by ultracentrifugation (20,000 × g for 5 min) at room temperature before ELISA test. The samples were diluted with Phosphate buffer (1:2) before analysis. The samples were analyzed using goat specific beta defensin–1 commercial kit (EO6D0419) as per the manufacturer’s instruction. The result showed that with supplementation of beta defensin-1 in goat semen, diluent maintains the concentration of beta defensin-1 even after cryopreservation. There was significant decrease (P